An Incomplete Spin Transition Associated with a Z′=1→Z′=24 Crystallographic Symmetry Breaking. Issue 20 (22nd November 2017) - Capel Berdiell, Izar; Kulmaczewski, Rafal; Cespedes, Oscar; Halcrow, Malcolm A.
Abstract: Crystalline [Fe L 2 ][BF4 ]2 ⋅ Me2 CO ( L=N ‐[2, 6‐dipyrazol‐1‐ylpyrid‐4‐yl]acetamide) is high‐spin at room temperature, and undergoes an abrupt, hysteretic spin‐crossover at T 1 / 2 =137 K (Δ T 1 / 2 =14 K) that proceeds to about 50 % completeness. This is associated with a crystallographic phase transition, from phase 1 ( P 21 / c, Z= 4) to phase 2 ( P 21, Z= 48). The cations associate into chains in the crystal through weak intermolecular π⋅⋅⋅π interactions. Phase 2 contains a mixture of high‐spin and low‐spin molecules, which are grouped into triads along these chains. The perchlorate salt [Fe L 2 ][ClO4 ]2 ⋅ Me2 CO also adopts phase 1 at room temperature but undergoes a different phase transition near 135 K to phase 3 ( P 21 / c, Z= 8) without a change in spin state. Abstract : Spinning around : The compound shown exhibits a hysteretic spin transition at T 1 / 2 =137 K, with about 50 % completeness. This is accompanied by a crystallographic phase change from P 21 / c, Z= 4 to P 21, Z= 48. The asymmetric unit of the low‐temperature phase is shown, with high‐spin (white), low‐spin (purple) and mixed spin‐state (pink) molecules highlighted. The isostructural ClO4 − salt undergoes a different phase change near 135 K, with no change of spin state.